A Case Against Crippling Compensation in International Law of State Responsibility. Issue 6 (15th July 2020) - Paparinskis, Martins
Abstract: The obligation of States to provide full reparation for internationally wrongful acts, including by full compensation, is one of the bedrock principles of international law. The article challenges this principle for cases where compensation is crippling for the responsible State or its peoples, which can occur when State responsibility is implemented before international courts and tribunals. The International Law Commission's decision not to qualify full reparation for instances of crippling compensation in its influential Articles on State responsibility was an unpersuasive legal position to adopt in 2001, and its rationale has aged badly. However, the failure by States and other actors to challenge it in the following two decades signified its endorsement by the international legal process. Nevertheless, the case against the permissibility of crippling compensation in modern international law can still be made, both on a case‐by‐case basis and at the level of customary secondary rules of State responsibility.